Analisis Sistem Dan Prosedur Dasi Sebagai Sarana Proses Pembayaran Klaim Santunan Asuransi Sosial Pada Pt Jasa Raharja Atas Korban Kecelakaan Lalu Lintas Di Kabupaten Pati - Jauhariyatun Nafi’ah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to find out and analyze the Jasa Raharja Corporate Data (DASI) system and procedures for Jasa Raharja Pati Regency. The research method used by the author is descriptive qualitative with the aim of knowing or analyzing events that occur in the field according to existing facts so that the true conditions can be known. In this report, researchers provide information according to what happened to the research object. Based on the research results, the use of DASI has been fully implemented and provides convenience felt by employees, namely the level of quality and work efficiency produced even though sometimes there are still some system or network problems. Apart from that, due to the large number of accident victims received, services need to be improved. The author considers that to maximize work performance and productivity, it is necessary to require more professional human resources in carrying out DASI operations.